Coping with functional interrelatedness and stakeholder fragmentation in planning at the infrastructure-land use interface: The potential merits of a design approach - Heeres, Niels; Van Dijk, Terry; Arts, Jos; Tillema, Taede (Journal of Transport and Land Use, 2016)
Road infrastructure projects are increasingly placed in their wider land-use context because of the functional relationships they have with surrounding areas. These more inclusive area-oriented planning processes typically involve a complex of interdependent but institutionally fragmented actors. Effective operationalization of collaborative strategies therefore remains difficult. Various policies introduce spatial design efforts to the infrastructure planning processes as a strategy to deal with these issues. This paper explores experiences in the Netherlands that have placed spatial design in vital positions in the process. An exploration of literature from the fields of spatial design, planning, and geography teaches us that design approaches, in such cases, may be applied to serve as a communicative modus that fosters dialogue, creativity, and eventually an inclusive and shared story about an area’s future. We interviewed designers experienced in serving that role and asked them whether and how such objectives are achieved. Consecutively, in order to come to practical lessons for exploitation of the merits indicated by the interviewees, we studied two projects that the interviewees considered best practices. We conclude that a combination of technical and relational design can effectively help a fragmented group of actors to find a shared and meaningful story and make integral choices on infrastructure projects, framed within a wider area’s development. Ensuring effective iterations between technical and relational design requires institutionalization of the coordinative capacities of design, as well as the right mindset among participants. This way, the employment of such design approaches facilitates effective operationalization of collaborative governance at the infrastructure/land-use interface.